2008
DOI: 10.1080/15368370802304155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Intermittent Exposure to AM Radiofrequency Field on Responses to Various Types of Noxious Stimuli in Growing Rats

Abstract: There are several reports of altered pain sensation after exposure (from a few minutes to hours in single or repeated doses for 2-3 weeks) to electromagnetic fields (EMF) in adults. The commonly utilized noxious stimulus is radiant heat. The nociceptive responses are known to be influenced by characteristics of stimulus, organism, and environment. We studied the pattern of nociceptive responses to various noxious stimuli in growing rats exposed to radiofrequency field (73.5 MHz amplitude modulated, 16 Hz power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Because of its dependency on local factors, the exposure estimates will need to be obtained on an individual level rather than relying on aggregated measures such as distance to transmission lines and transformers (Breckenkamp et al, 2008;Duyan et al, 2008;Maslanyj et al, 2009). Further complications in exposure estimation will be introduced as , even though some data suggest biological systems might be especially susceptible to non-linear 'resonant' frequency-amplitude combinations (Zhadin, 2001;Binhi and Savin, 2002), biological effects from HFVT might be caused by the intermittent nature of HFVT compared to the LF-RF frequency harmonic sine waves that carry the transients (Ivancsits et al, 2002;Mathur, 2008). These factors will most likely only further increase the potential for exposure misclassification in studies relating ''standard'' EMF exposure metrics to health effects (Kheifets et al, 2009;Schuz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its dependency on local factors, the exposure estimates will need to be obtained on an individual level rather than relying on aggregated measures such as distance to transmission lines and transformers (Breckenkamp et al, 2008;Duyan et al, 2008;Maslanyj et al, 2009). Further complications in exposure estimation will be introduced as , even though some data suggest biological systems might be especially susceptible to non-linear 'resonant' frequency-amplitude combinations (Zhadin, 2001;Binhi and Savin, 2002), biological effects from HFVT might be caused by the intermittent nature of HFVT compared to the LF-RF frequency harmonic sine waves that carry the transients (Ivancsits et al, 2002;Mathur, 2008). These factors will most likely only further increase the potential for exposure misclassification in studies relating ''standard'' EMF exposure metrics to health effects (Kheifets et al, 2009;Schuz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In previous data in healthy volunteers, cutaneous thermal pain perception was influenced by an overtime effect of head RF-EMF exposure (UMTS 1947 MHz, 1.75 W/kg) using visual analogue subjective pain rating scale [ 13 ]. In rodents, Mathur et al [ 14 ] showed that intermittent RF-EMF exposures (0.4 W/kg, 73.5 MHz, whole body) heightened the emotional component of phasic pain. Bodera et al [ 15 ] showed that RF-EMF exposures (1500 MHz and 1800 MHz) transiently suppressed the effect of tramadol, an analgesic acting through opioids and monoaminergic transmissions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, acute exposure (30 min) of specific ELF MFs demonstrated consistent inhibitory effect on opioid-induced analgesia [ 7 , 8 , 9 , 10 ]. In peripubertal rats, the chronic (45 days) and intermittent (2 h/day) exposure to amplitude modulated RF EMF facilitated the emotional component of phasic pain, while late responses to tonic pain stimuli were decreased [ 11 ].…”
Section: Introductionmentioning
confidence: 99%